Engine performance and emission characteristics of palm biodiesel blends with graphene oxide nanoplatelets and dimethyl carbonate additives. (15th March 2021) - Razzaq, L.; Mujtaba, M.A.; Soudagar, Manzoore Elahi M.; Ahmed, Waqar; Fayaz, H.; Bashir, Shahid; Fattah, I.M. Rizwanul; Ong, Hwai Chyuan; Shahapurkar, Kiran; Afzal, Asif; Wageh, S.; Al-Ghamdi, Ahmed; et al.
Abstract: This study investigated the engine performance and emission characteristics of biodiesel blends with combined Graphene oxide nanoplatelets (GNPs) and 10% v/v dimethyl carbonate (DMC) as fuel additives as well as analysed the tribological characteristics of those blends. 10% by volume DMC was mixed with 30% palm oil biodiesel blends with diesel. Three different concentrations (40, 80 and 120 ppm) of GNPs were added to these blends via the ultrasonication process to prepare the nanofuels. Sodium dodecyl sulphate (SDS) surfactant was added to improve the stability of these blends. GNPs were characterised using Scanning Electron Microscope (SEM) and Fourier Transform Infrared (FTIR), while the viscosity of nanofuels was investigated by rheometer. UV-spectrometry was used to determine the stability of these nanoplatelets. A ratio of 1:4 GNP: SDS was found to produce maximum stability in biodiesel. Performance and emissions characteristics of these nanofuels have been investigated in a four-stroke compression ignition engine. The maximum reduction in BSFC of 5.05% and the maximum BTE of 22.80% was for B30GNP40DMC10 compared to all other tested blends. A reduction in HC (25%) and CO (4.41%) were observed for B30DMC10, while a reduction in NOx of 3.65% was observed for B30GNP40DMC10. The diesel-biodiesel fuel blends with the addition of GNP exhibited a promising reduction in the average coefficient of friction 15.05%, 8.68% and 3.61% for 120, 80 and 40 ppm concentrations compared to B30. Thus, combined GNP and DMC showed excellent potential for utilisation in diesel engine operation. Highlights: Influence of Graphene oxide nanoplatelets (GNPs) and dimethyl carbonate (DMC) were studied. Surfactant sodium dodecyl sulphate (SDS) was used to stabilise the blend. The best ratio of GNP to SDS was 1:4 for maximum stability in biodiesel. Maximum reduction in BSFC and maximum BTE was observed for B30GNP40DMC10. B30GNP120DMC10 fuel blend showed a maximum reduction of 15.05% in COF.